Growth and function of spines in Jurassic and Cretaceous ammonites - Ifrim, Christina; Bengtson, Peter; Schweigert, Günter (Cretaceous research, 2018)
Spinose ammonoids occur in Earth history from the origin to the extinction of the subclass. In many cases, entire groups were concerned. The growth of spines in Kimmeridgian (Jurassic) aspidoceratids are described, discussed, and their construction and possible functions are compared with those of euomphaloceratine ammonites from the lower Turonian (Cretaceous) of Mexico, Venezuela and Brazil, and with those of collignoniceratid ammonites from the lower Coniacian of Venezuela. The basic construction of spines is similar in all taxa, irrespective of their position, length or the geological age of the taxon. It is suggested that shell secretion for spine formation may have been rapid compared with that of the rest of the shell. Spines do not appear to have been suitable for protection against predators or for a demersal or epibenthic mode of life. Instead, a sensory function is probable, but only for the outermost one to three pairs of spines near the aperture. An increased weight of the body chamber and increased friction during rocking motions and thus a stabilization of the shell in the open-water column are additional plausible explanations for the function of spines sealed by a basal septum.
Available online: 8 May 2017
Gesehen am 12.09.2019